KONTRUKSI REALITAS SOSIAL PADA IKLAN KAMPANYE DIESEL: BE A FOLLOWER - Sophia Purbasari (Universitas Informatika dan Bisnis Indonesia, 2021)
This research aims to analyze the socio-cultural construction of reality on commercial products of Brand Diesel with their campaign commercial ads series Diesel:Be A Follower. Social and cultural construction of the products seen as a sign, as well as sign language as verbal, so businesses advertising media construct social and cultural meanings inherent in a sign that structured products in the minds of consumers. Using a qualitative approach, data collected through the recording commercials advertising television. The study uses a review semiotics Barthes as a method for analyzing the layers of meaning as a sign of reality (reality of denotation, connotation and myth). The results showed that the advertisers have done a variety of ways persuasive to lead the consumer to use the product promoted, so that the function of advertising is done by the manufacturer does not emphasize on functionality or usability of the product but the social-cultural function is constructed, how to be a sign of the structure, and natural as well as the language used in the communication. Advertising messages has become a socio-cultural meanings of consumption for consumers who then applied these meanings to the social and cultural life as a natural thing